2020
DOI: 10.18203/2320-6012.ijrms20203089
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills of female health workers regarding selected non communicable diseases risk reduction and client satisfaction: a pilot study from western part of Rajasthan, India

Abstract: Background: The increasing burden of Non communicable diseases calls for added role on the part of health professionals. The female Health workers being the closest to population play an important role in alleviating the problem to great extent. Objective of this study was to assess the Knowledge, and skills of female health workers (FHWs) regarding selected non communicable diseases risk reduction and the client satisfaction with NCD skill services performed by FHWs.Methods: This study was undertaken at selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
5
1
Order By: Relevance
“…We observed that 75% of the ANMs of our study demonstrated satisfactory to excellent proficiency in RBS measurement, which was in line with the observations of Nebhinani et al [9] (76.5%). Concerning BP measurement, the skill level of ANMs (58.3%) in the present study was quite less compared to Nebhinani et al [9] (76.5%). The variability of observations might have been incurred due to differences in study settings, study subjects, checklist used for ascertainment of skill adequacy, etc.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that 75% of the ANMs of our study demonstrated satisfactory to excellent proficiency in RBS measurement, which was in line with the observations of Nebhinani et al [9] (76.5%). Concerning BP measurement, the skill level of ANMs (58.3%) in the present study was quite less compared to Nebhinani et al [9] (76.5%). The variability of observations might have been incurred due to differences in study settings, study subjects, checklist used for ascertainment of skill adequacy, etc.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 92.3%, 100.0% and 58.3% of the ANMs showed satisfactory to excellent proficiency in weight, height and WC measurement, respectively, which were more compared to the observations of Nebhinani et al [9] , where 64.7%, 58.3% and 5.9% of the front-line workers (FLWs) demonstrated adequate skills for the same, respectively. We observed that 75% of the ANMs of our study demonstrated satisfactory to excellent proficiency in RBS measurement, which was in line with the observations of Nebhinani et al [9] (76.5%). Concerning BP measurement, the skill level of ANMs (58.3%) in the present study was quite less compared to Nebhinani et al [9] (76.5%).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A previous survey of COVID-19 indicated that the perception of female healthcare workers was more adequate than that of male healthcare workers (Almohammed et al 2021 ). Moreover, Nebhinani and Saini revealed that female healthcare workers more strongly perceived NCD (non-communicable disease) related information (Nebhinani and Saini 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to less information dissemination concerning T2DM and the difference in the study population in which the study was conducted among subjects with diabetes and their family members. On the other hand, this result is higher than the study conducted in Stalowa Wola, Poland [30%] (29), Saudi Arabia 29.6% -42.6 % (30, 31), 25.4 % in rural Tanzania (61), 19.6% in south western Nigeria (15), Indian western Rajasthan [17.6%] (32), Bangladesh [13%] (18), 17.3% in Mekele and 5 % in West Go jam (33, 34), Nepal [5.5-20%] (21, 35), and Japan [2.47%] (36). This inconsistency might be due to the sociocultural difference between the populations.…”
Section: Discussionmentioning
confidence: 74%